The Influence of Work Environment and Career Advancement on Motivation and Its Implications on Bank Worker Performing - Ansori, Khoiron; Zahari, M.; Akbar, Ali (Dinasti International Journal of Management Science, 2026)
The purpose of this study is to examine how career advancement and the work environment affect worker motivation and how that affects performing at the Main Branch Office of Bank Jambi. This study employed a survey method together with a descriptive and quantitative methodology. The 59 workers of Bank Jambi's Central Head Office made up the population in this study, and the entire population was used as a sample (saturated sample). Questionnaires created using the indices of each variable were distributed in order to collect data, and their legitimacy and dependability were examined. In order to investigate the causal link within factors and the function of work motivation as a contributing variable, the data analysis employed PLS (partial least squares) analysis with the aid of SmartPLS software. The findings demonstrated that worker work motivation was positively and significantly impacted by career growth and the workplace. Additionally, it has been demonstrated that work motivation significantly and favorably affects worker performing. Additionally, the indirect impact test results showed that work motivation acted as a Intermediary variable within the work environment and advancement in career and worker performing. The study's conclusions show that a supportive workplace and a transparent, long-lasting career advancement program can boost worker motivation, which in turn affects productivity. In order to sustainably boost worker performing, Bank Jambi's Main Head Office is anticipated to keep bolstering its HRM policies, which are focused on enhancing the workplace and career advancement.